Uloha infekcie a zápalu v patogenéze aterosklerózy - Jaber, J; Murín, J; Kinová, S; Gavorník, P; Ghanem Wisam, M A; Radman, A; Gharaibeh, A; Richter, P (Vnitrni lekarstvi, 2002)
Pathogenesis of the atherosclerotic process is deemed as multifactorial. To the most important risk factors, besides certain family predisposition, there belongs hypercholesterolemia, arterial hypertension, obesity, diabetes mellitus, smoking and others. In the last years there are more and more data about the role of inflammation and infection in the whole development of atherosclerosis. The witness for this hypothesis is the findings of high parameters of inflammation in involved vessels as well as in the blood of atherosclerosis suffering persons. Opinions about the inflammation theory appear from the 90th. Local sterile inflammation in the subendotelium of the middle and big arteries has been proved to consist of specific immune reaction (activation of the T-lymphocytes) as well as nonspecific characteristic by elevated monocytes in the artery wall during the whole process of atherogenesis. Inflammation in the plaque can trigger and hold several factors engaged in the atherosclerotic process, such as oxidized LDL cholesterol, elevated production of various superoxides, activated macrophages, activated T-lymphocytes, cytokines (IL-1, IL-6, interferon gamma) and lipoprotein Lp (a). In this inflammation process levels of CRP (acute phase protein), fibrinogen and erythrocyte sedimentation are elevated as a reaction of the organism to nonspecific chronic infections. Because of this it is thought that elevated fibrinogen and erythrocyte sedimentation are markers of the cardiovascular risk. Some papers deal with antiinflammatory effects of statins, because these lower CRP levels so they also lower atherosclerotic risk through not only lowering of cholesterol levels. Also asprine, as an antiinflammation agent, changing the CRP levels, would be of benefit for patients with vascular disease because its antiaggregation and antiinflammatory effects. ACE inhibitors are also antiinflamatory through blocking of tissue production of angiotensin II (artery wall and atherosclerotic plaque). Enzymatic inhibitors changing angiotensin can also have a partial antiinflammatory effect. The infection theory is supported also by tracing of some microorganisms in the atherosclerotic plaque or in the blood, as e.g. Helicobacter pylori or Chlamydia pneumoniae; to the autoimmune origin is indicated the presence of the specific immunity reaction against heat shock proteins (HSP) or oxidized LDL. This infection theory offers new therapy possibilities. Therefore eradication for example by antibiotics can lead to stabilization of the atherosclerotic plaque with positive consequences, as it was discovered by many studies.
Keywords: Bacterial Infections; arterioskleróza; Animals; Inflammation; Humans; Blood Vessels; lidé; zánět; Arteriosclerosis; zvířata; cévy; bakteriální infekce